1994
DOI: 10.1111/j.1365-2958.1994.tb00460.x
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuations in glycolytic mRNA levels during morphogenesis in Candida albicans reflect underlying changes in growth and are not a response to cellular dimorphism

Abstract: The levels of pyruvate kinase (PYK1), alcohol dehydrogenase (ADH1), phosphoglycerate kinase (PGK1) and phosphoglycerate mutase (GPM1) mRNAs were measured during batch growth and during the yeast-to-hyphal transition in Candida albicans. The four mRNAs behaved in a similar fashion. PYK1, ADH1, PGK1 and GPM1 mRNA levels were shown to increase dramatically during the exponential growth phase of the yeast form, and then to decrease to relatively low levels in the stationary phase. The dimorphic transition was indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
57
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 47 publications
3
57
0
1
Order By: Relevance
“…Reprobing of the same filters revealed that the PYK1 mRNA also was repressed under identical conditions (Fig. 6) but the ADH1 mRNA was not repressed by heat shock (55). Therefore, the decrease in RP10 mRNA levels observed at 37ЊC during the dimorphism experiments (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 4 more Smart Citations
“…Reprobing of the same filters revealed that the PYK1 mRNA also was repressed under identical conditions (Fig. 6) but the ADH1 mRNA was not repressed by heat shock (55). Therefore, the decrease in RP10 mRNA levels observed at 37ЊC during the dimorphism experiments (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…Like RP10, the mRNAs encoding actin (ACT1) and the essential fungal translation elongation factor 3 (TEF3) increased when late-exponential-phase cells were inoculated into fresh medium (54). In contrast, the levels of the glycolytic mRNAs GPM1, PGK1, PYK1, and ADH1 decreased transiently under identical conditions (55).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations